2013
DOI: 10.1177/0305735612469674
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of harmony: The social and organisational factors in a professional vocal ensemble

Abstract: How do chamber music ensembles consistently succeed in achieving a level of harmony that many other work groups can only dream of? Through an in-depth case study of a professional vocal ensemble, this study explores some of the factors that underlie the excellence of chamber music ensembles as work groups. Qualitative interview data revealed information about member characteristics, leadership models, task distribution, decision making, relationships, conflicts, the artistic production process, characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
1
25
0
2
Order By: Relevance
“…Performing artists are also exposed to a number of interpersonal demands and are required to maintain a multiplicity of relationships, including those with colleagues, peers, management and audiences, who may have different and conflicting agendas. Researchers have reported that positive interpersonal relationships with colleagues are necessary for a harmonious working environment and also affect the quality of the artistic product (Lim, 2014; Dobson and Gaunt, 2015). Interpersonal skills are particularly tested when performing artists are transitioning into the profession and seeking new employment opportunities, particularly when in a freelance capacity (Dobson, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Performing artists are also exposed to a number of interpersonal demands and are required to maintain a multiplicity of relationships, including those with colleagues, peers, management and audiences, who may have different and conflicting agendas. Researchers have reported that positive interpersonal relationships with colleagues are necessary for a harmonious working environment and also affect the quality of the artistic product (Lim, 2014; Dobson and Gaunt, 2015). Interpersonal skills are particularly tested when performing artists are transitioning into the profession and seeking new employment opportunities, particularly when in a freelance capacity (Dobson, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Exploring different theoretical knowledge of musical collectives, it is concluded that it is a unique structure in which different individuals are tied to each other in different contexts (Lim, 2014). They are organized into groups, formed as a personality (Argyris, 1985;Garleja, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In any educational program level creation of collective, musical and mutual is an important skill set of unique individuals -self-realization and mutual affection (Lim 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Attaining excellence in ensemble playing depends on finding a balance between individual performance and interaction (Lim, 2014). This research investigates how singers influence each other in terms of intonation and pitch variation.…”
Section: Introductionmentioning
confidence: 99%